Dentistry and rheumatology collaboration: dental health, treatment and measures for osteonecrosis of jaw for patients with vasculitis - Acar, Buket; Akman, Abdullah C. (Acta Medica, 2025)
The relation between rheumatology and dentistry has increasing clinical importance, particularly in patients with systemic autoimmune diseases such as rheumatologic disorders and vasculitis. Periodontitis is a chronic inflammatory disease characterized by the progressive destruction of periodontal supporting tissues, occurring from a dysbiotic shift within the oral microbiota. Although the primary etiological factor of periodontal disease is bacterial plaque, the main factor causing breakdown in the periodontium is the host-mediated immunoinflammatory response. Periodontal diseases can have both direct and indirect impacts on overall systemic health through possible remote effects of the inflammatory response caused by bacterial infection of the periodontium, and serving as a risk factor for systemic diseases or conditions affecting general health. Oral lesions may develop in patients with vasculitis during the course of the disease, and oral findings may even be the first clinical findings before the diagnosis. Bone-modifying agents (BMAs) such as bisphosphonates, used to prevent osteoporosis associated with various autoimmune and immune-mediated inflammatory disease, can predispose individuals to complications affecting bone metabolism and oral health, including medication-related osteonecrosis of the jaw (MRONJ). In such cases, effective prevention, early diagnosis and multidisciplinary management are essential to reduce morbidity and maintain oral function. The present review aims to evaluate the potential interactions between periodontitis and rheumatological diseases; to assess the etiological/pathological basis of these diseases and the multidisciplinary approaches between periodontal and rheumatologic disciplines in promoting oral health and reducing the risk of osteonecrosis in patients with vasculitis.